A Teaching Model of Cultural and Creative Design Based on the Philosophy of the Book of Changes - Wen-Ting Fang; Jian-Hua Sun; Pei-Hao Tong; Yen-Yu Kang (Education Sciences, 2023)
In essence, cultural and creative design features humanity and culture. The process of how to transform culture into creativity is an essential subject of design education, which, in turn, calls for a new design teaching system. In regard to combining traditional Chinese thinking with modern design experience, the question of how to apply traditional Chinese thinking to design concepts, methods, and education is systematically explored in this research. Firstly, the question of how to transform the philosophy of “Tao, Vessel, Change and Comprehensiveness” in the Book of Changes into “design thinking” in order to establish the learning process of creative design with added value—as well as to set up the teaching model of cultural and creative design under “Tao, Vessel, Change and Comprehensiveness”—is discussed. After this, two cases of the Aboriginal Harvest Festival’s cultural creativity “Dancing Together” candlestick and the animation, cultural, and creative design of the “Wind Lion God” are used in order to examine the effectiveness of the specific design and to verify the feasibility of this teaching model in the development and application of cultural and creative products. The results demonstrate the feasibility of this teaching model, which provides a new systematic approach for the purposes of teaching and practice in the field of cultural and creative design.